Analysis of the Phenotypic Variability as Well as Impact of Early Diagnosis and Treatment in Six Affected Families With ALDH7A1 Deficiency - Jiao, Xianru; Gong, Pan; Wu, Ye; Zhang, Yuehua; Yang, Zhixian (Frontiers in Genetics, 2021)
Objective To describe the clinical characteristics of 12 patients from six families with pyridoxine-dependent epilepsy (PDE) carrying ALDH7A1 mutations, and analyze the impact of early diagnosis and treatment, as well as possible genotype-phenotype relationship. Methods Clinical and genetics data of 12 patients were collected. Results Family 1-3 presented with symptoms in the neonatal period, while family 4-6 presented during early infancy. In the same family, the age of onset was similar. The focal motor seizure appeared in all patients. The affected identical twins from family 4 were diagnosed with infantile spasms. Mutation analysis identified nine different ALDH7A1 mutations among six families. The neurodevelopment of siblings in family 1 was mild delay and normal separately due to the minor difference of delayed diagnosis time. Siblings in family 2 showed severely delayed and normal development respectively due to the significant difference of a delayed diagnosis for four years. In family 5, although the difference of the delayed diagnosis time is up to seven years, the nearly normal psychomotor development in both patients might be due to infrequent seizures before the delayed diagnosis. A severe phenotype exhibited in family 3, 4, and 6. The survived affected patients presented with severe developmental delay or refractory seizures and their twins or older sisters presented a similar clinical history and died in the early days of life. Mutation analysis showed D511N and IVS11+1G>A in family 3, V188A and exon1 deletion in family 4 , and Y354C and exon 8-13 deletion in family 6. Conclusion Patients from the same family often have the same phenotype, including onset age and seizure type. Early treatment with pyridoxine and infrequent seizures showed positive relationship with prognosis. The deletion of exon 1 and exon 8-13 might be associated with the severe phenotype.